Dealing with difficult teachers - Whitaker, Todd, 1959- (New York Routledge, 2015)
"This bestselling book provides tips and strategies to help school leaders improve, neutralize, or eliminate resistant and negative teachers. Learn how to handle staff members who * gossip in the teacher's lounge * consistently say "it won't work" when any new idea is suggested * send an excessive number of students to your office for disciplinary reasons * undermine your efforts toward school improvement * negatively influence other staff members. New to the third edition: A special section called Strategy Session, designed to help you figure out whether the challenging staff members are unaware of the effects of their actions or whether they are intentionally working against the school and more importantly, the students. You'll learn how to make that determination and what to do about it"--
Includes bibliographical references.
Keywords: Teacher effectiveness -- United States; Teacher-principal relationships -- United States; Teachers -- Dismissal of -- United States; School personnel management -- United States; EDUCATION / General; EDUCATION / Parent Participation; EDUCATION / Leadership